Impact of online education on fear of academic delay and psychological distress among university students following one year of COVID-19 outbreak in Bangladesh - Md. Jamal Hossain; Foyez Ahmmed; S.M. Abdur Rahman; Sherejad Sanam; Talha Bin Emran; Saikat Mitra (Heliyon, 2021)
Objectives: Extreme fear of academic delay (FAD) and psychological distress among students have arisen as great public health concerns worldwide due to the devastating actions of coronavirus disease 2019 (COVID-19). The precise aim of this study was to assess the impact of ongoing online education on current university students’ FAD and psychological stress symptoms following one year of calamitous COVID-19 outbreak in Bangladesh. Methods: A cross-sectional web-based survey was conducted from March 15 to 30, 2021, for data collection through a snowball simple sampling technique among Bangladeshi University students, where a total of 1,299 respondents (age: ≥ 18 years) responded in the questionnaire. After obtaining informed consent from the participants, we evaluated the association of various sociodemographic factors and the effects of current e-Learning activities on FAD and subsequent psychological distress among university students in Bangladesh. After excluding the partial responses (n = 177), we analyzed the clean data sheet (n = 1,122) by three consecutive statistical methods: univariate, bivariate, and multivariate analyses. Results: Alarmingly, near 60% of the current students exerted extreme FAD and were suffering from severe stress. Besides, 78.1% of students having severe FAD were severely psychologically stressed. Logistic regression analyses revealed that the students of the female gender, rural area, lower-income families, and who suffered from the highest FAD were more significantly (p < 0.05) stressed than their reference groups. Conclusion: The current analysis demonstrates that most Bangladeshi university students are battling with the unrivaled trend of FAD and facing severe psychological stress symptoms, which must be alleviated by the concerted efforts of the Government, Universities, and educationalists.